Pancreatic lipomatosis with massive steatorrhea. - Khan, NA; Amin, MS; Islam, MZ (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):712-4 The abstract of this article is available on the PubMed websiteRa